The sullivanians eaudiobook Sex, psychotherapy, and the wild life of an american commune. - Stille, Alexander (HighBridge Audio, 2023)
In the middle of the Ozzie and Harriet 1950s, the birth control pill became available and a maverick psychoanalytic institute, the Sullivan Institute for Research in Psychoanalysis, opened its doors in New York City. Its founders wanted to start a revolution, one grounded in ideals of creative expression, sexual liberation, and freedom from societal norms, and the revolution needed to begin at home. Dismantling the nuclear family would free kids from the repressive forces of their parents. The movement attracted many brilliant people as patients, including the painter Jackson Pollock and a swarm of other artists, the singer Judy Collins, and the dancer Lucinda Childs. By the 1960s, it had become an urban commune of hundreds of people, with patients living with other patients, leading a creative, polyamorous life. By the mid-1970s, under the leadership of Saul Newton, it devolved from a radical communal experiment into an insular cult, with therapists controlling virtually every aspect of their patients' lives, from where they lived to how often they saw their children. Although the group was highly secretive, even after its dissolution in 1991, Alexander Stille has reconstructed the inner life of this hidden parallel world. Through countless interviews and personal papers, The Sullivanians reveals the story of a fallen utopia in the heart of New York City.